First-in-human CLDN18.2 functional diagnostic pet imaging of digestive system neoplasms enables whole-body target mapping and lesion detection. - Wang, Shujing; Qi, Changsong; Ding, Jin; Li, Dan; Zhang, Miao; Ji, Congcong; Jiang, Fangli; Teng, Fei; Yu, Jie; Qian, Xueming; Wang, Feng; Shen, Lin; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2023)
Purpose: Claudin 18.2 (CLDN18.2) is a reliable target for lesion detection and could have clinical implications for epithelial tumors, especially digestive system neoplasms. However, there is no predictive technology for accurate whole-body mapping of CLDN18.2 expression in patients. This study assessed the safety of the 124I-18B10(10L) tracer and the feasibility of mapping whole-body CLDN18.2 expression using PET functional imaging. Methods: The 124I-18B10(10L) probe was synthesized manually, and preclinical experiments including binding affinity and specific targeting ability were conducted after testing in vitro model cells. Patients with pathologically confirmed digestive system neoplasms were enrolled in an ongoing, open-label, single-arm, first-in-human (FiH) phase 0 trial (NCT04883970). 124I-18B10(10L) PET/CT or PET/MR and 18F-FDG PET were performed within one week. Results: 124I-18B10(10L) was successfully constructed with an over 95% radiochemical yield. The results of preclinical experiments showed that it had high stability in saline and high affinity in CLDN18.2 overexpressing cells (Kd = 4.11 nM). Seventeen patients, including 12 with gastric cancers, 4 with pancreatic cancers, and 1 with cholangiocarcinoma were enrolled. 124I-18B10(10L) displayed high uptake in the spleen and liver, and slight uptake in the bone marrow, lung, stomach and pancreas. The tracer uptake SUVmax in tumor lesions ranged from 0.4 to 19.5. Compared with that in lesions that had been treated with CLDN18.2-targeted therapy, 124I-18B10(10L) uptake was significantly higher in lesions that had not. Regional 124I-18B10(10L) PET/MR in two patients showed high tracer uptake in metastatic lymph nodes. Conclusions: 124I-18B10(10L) was successfully prepared and exhibited a high binding affinity and CLDN18.2 specificity in preclinical studies. As an FiH CLDN18.2 PET tracer, 124I-18B10(10L) was shown to be safe with acceptable dosimetry and to clearly reveal most lesions overexpressing CLDN18.2. Trial registration: NCT04883970; URL: https://register.clinicaltrials.gov/. Registered 07 May 2021.